KAJIAN EMPIRIS MODEL EVALUASI KIRKPATRICK UNTUK MENGUKUR EFEKTIVITAS PELATIHAN KERJA SECARA DARING - Islami, Gogon; Nugroho, Dian Ari (Jurnal Kewirausahaan dan Inovasi, 2022)
This research is an evaluative applied research that aims to evaluate the effectiveness of online training activities for interns at Bank Sinarmas Syariah using the Kirkpatrick evaluation model which measures the effectiveness of four levels, namely reaction, learning, attitude, and outcome. This study uses a mixed quantitative and qualitative approach with a sequential explanatory strategy. Analysis of quantitative data used is quantitative descriptive. Data were obtained from 49 job training participants. In the level of reaction, learning and attitude obtained satisfactory evaluation results, while the level of results obtained satisfactory but not optimal results. Qualitative methods are needed as a follow-up to the findings of quantitative methods to answer research problems in a more solution way. The results of the qualitative research conclude that the management of the implementation of job training has been quite good but there are still obstacles caused by its implementation online. Online job training has a positive effect on job readiness assisted by mentoring activities. The heterogeneity of employee performance that occurs is caused by the placement function that is not in accordance with the job analysis as the main factor, followed by differences in motivation and field constraints.